Airway challenges in bilateral temporomandibular joint ankylosis with adenoid hypertrophy: a case report - Gaurav Jain; Amiya Kumar Barik; Amrita Banerjee; Naveen S; Ashi Chug (Elsevier, 2019)
Temporomandibular joint ankylosis is one of the most challenging airway disorders associated with varying anatomical abnormalities like adenotonsillar hypertrophy, craniofacial malformations, macroglossia, etc. This case highlights the intubation difficulties confronted during the airway management of a 10-year-old girl presenting lately with bilateral temporomandibular joint ankylosis, hypoplastic mandible, and adenoid hypertrophy. This patient was intubated successfully by using a suction catheter assembly to negotiate the endotracheal tube across the adenoid, and an unmatched-size flexible intubation fiberscope through a "separate insertion" technique and external laryngeal manipulation. This case emphasises the significance of a comprehensive preoperative evaluation in preparing the anaesthetic plan of an anticipated difficult airway in a paediatric population, having diverse anatomical hurdles presenting concurrently.